2020
DOI: 10.3390/cancers12010124
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism in Cancer: The Roles of STAT3 and STAT5 in the Regulation of Metabolism-Related Genes

Abstract: A central characteristic of many types of cancer is altered energy metabolism processes such as enhanced glucose uptake and glycolysis and decreased oxidative metabolism. The regulation of energy metabolism is an elaborate process involving regulatory proteins such as HIF (pro-metastatic protein), which reduces oxidative metabolism, and some other proteins such as tumour suppressors that promote oxidative phosphorylation. In recent years, it has been demonstrated that signal transducer and activator of transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 181 publications
1
38
0
Order By: Relevance
“…Previous studies have demonstrated that abnormal metabolism is one of the markers of cancer cells, and that there are differences between healthy and tumor cells in energy metabolism (58)(59)(60); in addition, various catabolic pathways, for example, glycolysis, OXPHOS and fatty acid metabolism, are involved in energy metabolism (61). In the current study, RNA-seq data were used to detect local energy metabolism-related gene expression status and their prognostic value for patients with ovarian cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated that abnormal metabolism is one of the markers of cancer cells, and that there are differences between healthy and tumor cells in energy metabolism (58)(59)(60); in addition, various catabolic pathways, for example, glycolysis, OXPHOS and fatty acid metabolism, are involved in energy metabolism (61). In the current study, RNA-seq data were used to detect local energy metabolism-related gene expression status and their prognostic value for patients with ovarian cancer.…”
Section: Discussionmentioning
confidence: 94%
“…The results from several studies indicate that STAT3 functions as an integration center for various cancer cell signals through its nuclear and mitochondrial activities. In recent years, a pro-oncogenic role for STAT3 serine phosphorylation has been widely reported, and is also reported to be associated with its functions in the mitochondria [ 111 ]. However, the mechanism by which STAT3 carries out its activities within the mitochondria remains unknown and controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, multiple studies have demonstrated that in the absence of a given STAT member, receptors will recruit other STAT members instead (Hennighausen et al, 2018;Yu et al, 2010;Valle & Soto et al, 2020;Hosui et al, 2009;Hin et al, 2020;Friedbichler et al, 2012). STAT5 and STAT3 are two proteins of STAT family that show high homology in their functional domains, can be activated by different mechanisms, and bind to distinct loci to regulate specific target gene expression .…”
Section: Discussionmentioning
confidence: 99%